2022
DOI: 10.1371/journal.pone.0257711
|View full text |Cite
|
Sign up to set email alerts
|

Cortical oscillatory dysfunction in Parkinson disease during movement activation and inhibition

Abstract: Response activation and inhibition are functions fundamental to executive control that are disrupted in Parkinson disease (PD). We used magnetoencephalography to examine event related changes in oscillatory power amplitude, peak latency and frequency in cortical networks subserving these functions and identified abnormalities associated with PD. Participants (N = 18 PD, 18 control) performed a cue/target task that required initiation of an un-cued movement (activation) or inhibition of a cued movement. Reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 157 publications
(209 reference statements)
1
1
0
Order By: Relevance
“…The unit population responses in Aux-KO mice exhibited delayed oscillation peaks, and slower oscillation frequencies, compared to the oscillations in WT. Such altered cortical oscillations were also reported in parkinsonian patients in different contexts, 70 , 71 suggesting temporally altered circuit activity. The shifted frequency of the familiarity-evoked oscillations in Aux-KO mice is similar to the previously described frequency shift in Fmr1 KO mice, which was accompanied by reduced functional connectivity between excitatory neurons and inhibitory neurons.…”
Section: Discussionsupporting
confidence: 56%
“…The unit population responses in Aux-KO mice exhibited delayed oscillation peaks, and slower oscillation frequencies, compared to the oscillations in WT. Such altered cortical oscillations were also reported in parkinsonian patients in different contexts, 70 , 71 suggesting temporally altered circuit activity. The shifted frequency of the familiarity-evoked oscillations in Aux-KO mice is similar to the previously described frequency shift in Fmr1 KO mice, which was accompanied by reduced functional connectivity between excitatory neurons and inhibitory neurons.…”
Section: Discussionsupporting
confidence: 56%
“…A study found increased functional connectivity between the limbic system (which is involved in emotion processing) and various cortical regions in anxious PD patients compared to PD patients without anxiety [ 25 ]. Another study using magnetoencephalography (MEG) found abnormal oscillatory power and functional connectivity in the frontal cortex of PD patients [ 26 ]. These findings suggest that there may be significant oscillation-specific node differences in the brains of PD patients with anxiety, which may account for the presence and severity of anxiety symptoms in these individuals.…”
Section: Discussionmentioning
confidence: 99%